The use of warm-ups in teaching English - Jiménez Atiaja, Jesús Fernando (2024)
In English language teaching, integrating warm-up activities is crucial for creating engaging and effective learning classes. The purpose of this research is to determine students' perceptions of the use of warm-ups in teaching the English language at Ramon Barba Naranjo Educative Unit in August 2023 and February 2024. This is a descriptive - quantitative study. The instrument for data collection was a survey with a questionnaire adapted from Lengari and Pavita (2023). The questions consisted of three categories: (1) warming up and principles, (2) background knowledge of warming up activities, (3) Motivation and warming ups. The participants were 90 male and 36 female students. The data were analyzed using the Excel program. This research showed that consistent and appropriate application of warm-up brings clear benefits. First, the application of warm-ups is beneficial when it is used or applied with correct principles. Second the warm-ups contribute to prepare the body and mind to keep them active and mentally prepared to start the class. It also helps to connect new knowledge with old one. In addition, warm-ups create a positive classroom environment perfect for interaction between students and teachers. Finally, warm-ups increase the motivation of the students by helping them to start the class with enthusiasm. Once the students feel motivated, they start to participate more in class and concentrate on learning more English. In conclusion, warm-ups in language teaching enhance class atmosphere, activate prior knowledge, and reinforce past lessons. They promote routine, communication, and language skill development. So, it is relevant to apply effective warm-ups in classes.